Linking public capital to economic performance - Public capital: The missing link between investment and economic growth - Sharon J. Erenburg (Levy Economics Institute of Bard College, 1994)
Following up on findings by J. Bradford DeLong and Lawrence Summers that a robust statistical relationship exists between productivity and private sector investment in plant and equipment, the author explores whether there is also a connection between economic growth and public spending. She argues that public investment in infrastructure stimulates private sector investment in plant and equipment. By providing empirical proof that public and private investment are complements in production, Erenburg supplies the missing link that explicitly ties public infrastructure to economic growth.
Keywords: 330